Effects of moment of inertia on restricted motion swing speed - Schorah, D.; Choppin, S.; James, D. (Sports Biomechanics, 2015)
In many sports, the maximum swing speed of a racket, club, or bat is a key performance parameter. Previous research in multiple sports supports the hypothesis of an inverse association between the swing speed and moment of inertia of an implement. The aim of this study was to rigorously test and quantify this relationship using a restricted swinging motion. Eight visually identical rods with a common mass but variable moment of inertia were manufactured. Motion capture technology was used to record eight participants' maximal effort swings with the rods. Strict exclusion criteria were applied to data that did not adhere to the prescribed movement pattern. The study found that for all participants, swing speed decreased with respect to moment of inertia according to a power relationship. However, in contrast to previous studies, the rate of decrease varied from participant to participant. With further analysis it was found that participants performed more consistently at the higher end of the moment of inertia range tested. The results support the inverse association between swing speed and moment of inertia but only for higher moment of inertia implements.